Children, education and empire in early Sierra Leone: left in our hands - Keefer, Katrina (Global Africa, 2019)
The founding of the Sierra Leone Colony, 1787-1808 -- A new kind of Protestantism in Sierra Leone -- The Church Missionary Society and its missionaries -- Bush schools, karanthes and mission schools -- The CMS school communities 1806-1819 -- The pupils at the mission schools -- The children of the CMS -- Mission education and leadership in transforming Sierra Leone